Histone Methylation Related Therapeutic Challenge in Cardiovascular Diseases - Yang, Yang; Luan, Ying; Yuan, Rui-Xia; Luan, Yi (Frontiers in Cardiovascular Medicine, 2021)
The epidemic of cardiovascular diseases (CVDs) is predicted to spread rapidly in advanced countries accompanied by the high prevalence of risk factors. In terms of pathogenesis, the pathophysiology of CVDs is featured by multiple disorders, including vascular inflammation accompanied by simultaneously perturbed pathways, such as cell death and acute/chronic inflammatory reactions. Epigenetic alteration is involved in the regulation of genome stabilization and cellular homeostasis. The association between CVD progression and histone modifications is widely known. Among the histone modifications, histone methylation is a reversible process involved in the development and homeostasis of the cardiovascular system. Abnormal methylation can promote CVD progression. This review discusses histone methylation and the enzymes involved in the cardiovascular system and determine the effects of histone methyltransferases and demethylases on the pathogenesis of CVDs. We will further demonstrate key proteins mediated by histone methylation in blood vessels and review histone methylation-mediated cardiomyocytes and cellular functions and pathways in CVDs. Finally, we will summarize the role of inhibitors of histone methylation and demethylation in CVDs and analyze their therapeutic potential, based on previous studies.